Pengaruh Word Of Mouth, Kualitas Pelayanan Dan Lokasi Terhadap Keputusan Pembelian Sego Sambel Cak Uut Malang - Puput Rismunawati; N. Rachma; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACT The research a purpose to knowing and analyze word of mouth, service quality and location of the purchasing decision of Malang Sambuk Malang, both partially and simultaneously. This research uses explanatory research with quantitative approach. The population in this studywasthe 2016 feb unisma studentswho had ever been culinaryin Malang Ural Malang. Samplestaken as many as 105 participants. The sampling techniq ueusedisthe Malhotratheory. Data were analyze dusing multiple linear regressionanalysi sprocessed with SPSS25 software. The data collection method used was a questionnaire. The results showed that Word of Mouth had no significanteffect partially on Purchasing Decisions. Meanwhile, Service Quality and Location have a partially significanteffect on Purchasing Decisions. And, Word of Mouth, Service Quality, Location has a significant simultaneouseffect on PurchasingDecisions. Keywords: Word of Mouth, Service Quality, Location and Purchasing Decisions.